Enhanced Photoelectrocatalytic Activities for CH3OH‐to‐HCHO Conversion on Fe2O3/MoO3: Fe‐O‐Mo Covalency Dominates the Intrinsic Activity - Huang, Sheng; Ouyang, Ting; Zheng, Bang‐Feng; Dan, Meng; Liu, Zhao‐Qing (Angewandte Chemie International Edition, 2021)
The catalytic conversion of alcohols under mild conditions is a great challenge because it is constrained by low selectivity and low activity. Herein, we demonstrate a hollow nanotube Fe2O3/MoO3 heterojunction (FeMo‐2) for the photoelectrocatalytic conversion of small‐molecule alcohols. Experimental and theoretical analyses reveal that the optical carrier transfer rate is enhanced by constructing interfacial internal electric fields and Fe‐O‐Mo charge transfer channels. For the formox process, heterojunctions possess superior HCHO‐selective reaction paths and free energy transitions, optimizing the selectivity of HCHO and enhancing the reactivity. FeMo‐2 shows a greatly improved performance compared to single Fe2O3; the photocurrent density of FeMo‐2 reaches 0.66 mA cm−2, which is 3.88 times that of Fe2O3 (0.17 mA cm−2), and the Faraday efficiency of the CH3OH‐to‐HCHO conversion is 95.7 %. This work may deepen our understanding of interfacial charge separation and has potential for the production of HCHO and for conversion reactions of other small‐molecule alcohols at cryogenic temperatures. A Z‐Scheme Fe2O3/MoO3 hollow nanotube with a CH3OH‐to‐HCHO selectivity of 95.7 % was developed. The thin‐walled hollow structure facilitates a fast transfer of photogenerated carriers and enhances light utilization. The Fe‐O‐Mo charge transfer channel and internal electric field in the Fe2O3/MoO3 interface improve the charge transfer efficiency. PEC experiments and calculations demonstrate that C−H bond breaking is the rate‐determining step.